Kajian Literatur Alasan Penggunaan Rokok Elektrik (Vape) Serta Dampaknya pada Generasi Z - Nayla Jasmine Fadillah; Risky Akaputra; Andriyani Andriyani (Jurnal Siti Rufaidah, 2025)
One way to convert conventional cigarettes to electronic cigarettes is by using vapes. Electronic cigarettes have been widely available since 2014 and have gained popularity among various customer demographics. The number of people using electronic cigarettes in Indonesia continues to increase every year. The trend of vape pods has gained popularity among Generation Z and other young generations. Many people use vape pods because they provide a variety of flavors and less concentrated smoke. The use of vapes, or electronic cigarettes, has become common among young Generation Z. The purpose of this study was to determine the substantial impact of vaping and smoking on the lifestyle of Generation Z. The methodology used was a literature review using a qualitative descriptive study approach. Literature analysis was conducted using fifteen publications from national and international databases, including Google Scholar and PubMed, published between 2020 and 2025. The findings of the review indicate that a number of factors, such as family, friends, and environment, influence vape user adherence.